Improving Junior High School Students English Speaking Skills Using the Speechace Application - Harahap, Arry Pauji; Ahmad Amin Dalimunthe (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The intent of the study was to examine the efficacy of using the Speech Ace program in enhancing the English oral proficiency of junior high school pupils. A quasi-experimental approach was used, consisting of one experimental class that included Speech Ace during sessions, and one control class that received standard education. Both courses underwent pre-testing and post-testing to assess their speaking abilities. The findings demonstrated a statistically significant enhancement in the average score of the experimental group's post-test, which increased from 75 to 88 (p=0.001). On the other hand, the control class did not show a notable variation in average scores, which ranged from 73 to 75 (p=0.05). A t-test analysis comparing independent samples showed a statistically significant difference between the groups, with a p-value of 0.000, which is less than the significance level of 0.05. As a result, it was determined that the study hypothesis was confirmed, indicating that SpeechAce had a considerable impact on students' English-speaking proficiency. The good evaluations of SpeechAce were also seen in the student interviews and surveys. In summary, the results of the study provide concrete evidence that using technology-based tools like SpeechAce may significantly improve students' pronunciation abilities when used with traditional teaching techniques.